Design study and scaled experiment of induction and synchronous motor for civil application of electromagnetic aircraft launch system - Bertola, Luca; Cox, Tom; Wheeler, Patrick; Garvey, Seamus D.; Morvan, Herve (2016)
The engine size of modern passenger transport aircraft is principally determined by take-off conditions, since initial acceleration requires maximum engine power. An Electromagnetic Launch (EML) system could provide some or all of the energy required at the launch stage so that the aircraft engine power requirement and fuel consumption may be significantly reduced. So far, EML for aircraft has been adopted only for military applications to replace steam catapults on the deck of aircraft carriers. This paper will describe the application of EML to propel civil aircraft on the runways of modern airports. A comparison of synchronous and asynchronous electrical motor systems designed to launch an A320-200 will be presented. The paper will present the solution of the transient heat transfer problem of EML systems and the respective design limitations of a civil aircraft launcher under rated current density. The experimental setup that will serve for future validation is introduced.